KONFLIK SOSIAL DALAM NOVEL TENTANG KAMU KARYA TERE LIYE: TINJAUAN SOSIOLOGI SASTRA - Siti Nurchanifah; Luluk Isani Kulup (Buana Bastra, 2018)
Humans as social beings must have experienced a contradiction or dispute. In the daily life of many people who experience social conflicts, both in real life and in literary works such as theater, film, novel, and so on. This research is motivated by the number of social conflicts in novel characters are no exception to the novel About You. The approach used in this research is the sociology of literature. Sociology of literature is an approach in analyzing literary works that talk about the relationship between the author's life with his social life. This study aims to describe social conflict in Tere Liye's novel About You. The research method used is descriptive qualitative research. The data in this study is data that tangible words, phrases, and sentences contained in Tere Liye's novel About You. The data obtained by using library techniques, refer to, and record. Data were analyzed using descriptive method. After the data were collected and analyzed, there were fifty-five data from the six social conflicts of Soekanto. The social conflict consists of poverty which includes property poverty, moral poverty, and religious poverty, crimes, family disorganization, the problems of young people in modern society, fights, and violations of community norms in the form of child prostitution and delinquency.